Capturing teacher priorities: Using real-world eye-tracking to investigate expert teacher priorities across two cultures. (April 2019) - McIntyre, Nora A.; Jarodzka, Halszka; Klassen, Robert M.
Abstract: Classroom teaching is complex. In the classroom, teachers must readily attend to disruptions and successfully convey new tasks and information. Outside the classroom, teachers must organise their priorities that are important for successful student learning. In fact, differing gaze patterns can reveal the varying priorities that teachers have. Teacher priorities are likely to vary with classroom expertise and can conceivably change with culture too. Therefore, the present study investigated expertise related and cultural teacher priorities by analysing their gaze proportions. To obtain this data, 40 secondary school teachers wore eye-tracking glasses during class time, with 20 teachers (10 expert; 10 novice) from the UK and 20 teachers (10 expert; 10 novice) from Hong Kong. We analysed gaze proportions during teachers' attentional (i.e., information-seeking, e.g., teacher questioning students) and communicative (i.e., information-giving, e.g., teacher lecturing students) gaze. Regardless of culture, expert teachers' gaze proportions revealed prioritisation of students, whereas novice teachers gave priority to non-instructional (i.e., not students, teacher materials, or student materials) classroom regions. Hong Kong teachers prioritised teacher materials (e.g., whiteboard) during communicative gaze whereas UK teachers prioritised non-instructional regions. Regarding culture-specific expertise, with Hong Kong experts prioritised teacher materials more than UK experts who, in turn, did so more than UK novices. We thus demonstrate the role of implicit teacher gaze measures as micro -level indicators of macro -level and explicit aspects of instruction, namely teacher priority. Highlights: Expert teachers prioritise students, regardless of culture. During communicative gaze, Hong Kong teachers prioritise teacher materials. During communicative gaze, UK teachers prioritise non-instructional regions. Prioritising teacher materials is a mark of Hong Kong teacher expertise.